(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: Analyzing the dose regimen of carbapenem antibiotics used in pediatric patients at Can Tho Children’s Hospital. Objects and methods: retrospective-descriptive study on 140 medical records of patients being treated at departments of Can Tho Children’s Hospital during the period from June 1st, 2020 to December 31st, 2020. Results: Regarding the dosage regimen characteristics of meropenem showed that 20.3% and 10.8% of meropenem’s indications for the dose of meropenem for non-central nervous system infections and meningitis treament was appropriate according to the recommendations. Meanwhile, up to 63.5% of the dose was higher than the recommended dose and 5.5% of the treatment dose was lower than the recommended dose. Regarding imipenem dosage regimen characteristics from the results showed that 71.2% of the dose of imipenem for the treatment of infections non-central nervous system complied with recommendations according to the literature. However, more than 20% of the recommended dose for patients was lower than recommended dose. Conclusion: The meropenem dose regimen was consistent with the recommendation was low. The imipenem dose regimen was consistent with the relatively high recommendation.